The Influence of Islamic Service Quality in Increasing Customer Loyalty (Case Study at Mandiri Utama Finance Jember) - Nafaqoh, Eno Barokatul; Nursyamsiyah, Siti; Bashori, Dhofir Catur (Wealth: Journal of Islamic Banking and Finance, 2025)
Competition in the business world is getting tighter. This competition requires business actors to be able to maximize company performance in order to compete in the market. PT Mandiri Utama Finance (MUF) is a subsidiary of PT Bank Mandiri (Persero) Tbk which is engaged in the vehicle financing sector to serve the needs of the people in Indonesia. This study aims to determine how the influence of Islamic service quality on increasing customer loyalty at PT Mandiri Utama Finance Jember Branch, this study focuses on increasing customer loyalty at Mandiri Utama Finance Jember, This type of research uses a quantitative method with a sample of 110 respondents and uses a sampling technique with Purposive sampling technique, using a data collection technique in the form of a questionnaire to respondents. The data analysis technique for this study uses instrument testing, classical assumptions and multiple linear regression, hypothesis testing and coefficient of determination R2 The results of the study show that Islamic service quality has a positive and significant effect on customer loyalty at PT Mandiri Utama Finance Jember. The contribution of the influence of Islamic service quality on customer loyalty reaches 96%, while the remaining 4% is influenced by other variables not observed in this study. Thus, the implementation of services based on Islamic values can significantly increase customer loyalty